Carbogenically coated silica nanoparticles and their forensic applications. Issue 53 (13th June 2016) - Fernandes, D.; Krysmann, M. J.; Kelarakis, A.
Abstract : The color-tunable C-SiO2 are ideal powders for fingerprint enhancement, and they can also generate self-assembled nanotags suitable for object authentication. Abstract : Carbogenically coated silica nanoparticles (C-SiO2 ) exhibit color-tunability and carry great promise for two important forensic applications. First, the C-SiO2 nanopowders are ideal for fingerprint development, yielding strong contrast against multicoloured and patterned backgrounds. Second, spontaneous nanoparticle aggregation leads to non-duplicable, inexpensive nanotags that can support sustainable technologies to combat counterfeiting.